Development of Ukraine higher education system for the balanced nature management - RIDEI, Nataliya; SHOFOLOV, Denys (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The development of a national system of education for sustainable naturalresources as a form of social activity has been theoretically proved and aimed atoptimizing management training environmental experts by improving its professionaloriented content, scientific, methodological and information support,structural and organizational structure for the intended purpose. It was determined that organizational and functional structure of environmental managementas a set of (system) levels in the unity of their functions, powers and organizationalrelations and provides a holistic effect on the social system and the environment.It was found that the theoretical foundation of management trainingproblem decision of future ecologists for the balanced nature management isa complex combination of approaches: system, ecosystem, system-structural,systemic-functional, competency, synergistic, axiological, acmeological, ecocentric,noosphere.